The effect of corporate social responsibility on brand awareness: Evidence from the insurance sector in Zimbabwe - Kudzaishe Charlotte Gaura; Wilbert Manyanga; Lovemore Chikazhe (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2021)
The aim of this study was to establish the effect of corporate social responsibility (donations, sponsorship and community involvement) on brand awareness within the insurance sector in Zimbabwe. Data was gathered from 350 insurance customers using a structured questionnaire with Likert-type questions. The findings show that corporate social responsibility positively infl uences brand awareness. The study contributes to studies that proved a significant relationship between corporate social responsibility and brand awareness in sectors other than the insurance sector. Thus, insurance firms are advised to seriously plough back proceeds to their communities.
Keywords: 650; corporate social responsibility; brand awareness; insurance sector; Zimbabwe